Neither with Lima nor with Madrid. Rural guerrillas in the war of independence of Peru - Escanilla Huerta, Silvia (2021)
Traditionally, the historiography of the independence of Peru has focused on the peoples’ desire (or lack thereof) of breaking free from the Spanish crown. Despite recent efforts to transcend dichotomous interpretations, there are still few studies that analyze why the people decided to participate in the war, regardless of the side they took. This article explores their motivation for participating in the war by analyzing the background of the social mobilization prior to the war, as well as the characteristics of guerrilla organization in rural Peru during the war of independence. By focusing on how people lived and experienced the war, this article demonstrates that guerrillas constituted a specific form of popular political participation, which were decisive in the definition of the war because they represented the emergence of autonomous local and regional powers within the vice regal space.